Pellets produzidos a partir da biomassa de capim elefante BRS Kurumi, lodo flotado e bagaço de mandioca - Juppa, Anna Maria; Andriola, Maria Paula; Oliveira Diaz de Lima, Victória; Bavaresco dos Santos, Aline; Caetano de Oliveira, Luciano; Ferla de Oliveira, Adriana (Latin American Journal of Energy Research, 2024)
Pellets are solid granulated biofuels produced from ground and compacted plant biomass. This research presents an alternative way of using BRS Kurumi elephant grass plant biomass, flooded sludge and cassava bagasse as a binder, with the aim of producing pellets. The pellets were characterized in terms of immediate analysis, bulk and apparent density, calorific value and energy density. It was observed that the pellets produced with 100% BRS Kurumi grass (TK) had a high ash content (14,66%), and with the addition of 20% flocculated sludge (TKL) this volue decreased (7,28%), increasing the fixed carbon content (18,14%), which consequently increased the higher calorifc value to 16.20MJ.Kg-1. With the addition of 2% cassava bagasse, the apparent energy density was 15.15GJ.m-3, while TKL showed 17.73 GJ.m-3. In general, all the proposed treatments are possible to carry out and have promising physicochemical and energy characteristics for use as solid biofuels.